A hierarchically structured and multifunctional membrane for water treatment - Bai, Hongwei (2013)
Currently, the biggest challenge for filtration membrane application is the severe membrane fouling problem, which consequently results in low flux and high energy cost. Herein, a novel kind of multifunctional membrane was fabricated via integrating the advantages of conventional polymer membrane as supporting layer and “forest” like hierarchically structured TiO2/ZnO nanomaterials as functional layer. This membrane has shown multifunctional properties, such as, high photocatalytic activity, high flux and high antibacterial capacity, which make it as a good candidate to tackle the challenge of producing clean water at a constant high flux with no membrane fouling problem and energy saving manner. The outstanding performance of this novel membrane would bring enough benefits to filtration membrane industry for clean water production and environmental protection.